Racionalidade e controle nos processos sociais notas para um plano de trabalho - Moraes, Reginaldo Carmello Correa de [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1984)
O autor expõe etapas que julga necessárias para o exame de modernas teorias a respeito das transformações econômicas, sociais e culturais da história brasileira. Por outro lado, esse movimento visaria investigar os fundamentos epistemológicos de tais explicações do Brasil. O texto corresponde, insiste-se, a um plano de trabalho.

The author exposes some stages judged necessary for the examination of the modern theories about the economic, social and cultural changes of brazilian history. on the other hand, this movement would have in view to search the epistemological grounds of such Brazil's explanations. This text, it must be remembered, presents it self only as a work plan.
Rationality and control in social processes - notes on a work plan
Keywords: Racionalidade histórica; processo social; fundamentos da explicação científica; filosofia da história; filosofia política; pensamento político brasileiro; planejamento; Historical reasonableness; social process; grounds of scientific explanation; philosophy of history; politic philosophy; brazilian politic thought; planning